Financial Statement Analysis - K.R. Subramanyam (Mc.Graw-Hill Education, 2015)
The ability to understand and analyze financial statements is important to effective decision making by investors, creditors, analysts, consultants and managers. Financial Statement Analysis equips students with the necessary skills to succeed in the increasingly competitive business environment. Financial statement analysis (or financial analysis) is the process of reviewing and analyzing a company's financial statements to make better economic decisions. These statements include the income statement, balance sheet, statement of cash flows, and astatement of changes in equity. Financial statement analysis is a method or process involving specific techniques for evaluating risks, performance, financial health, and future prospects of an organization